Moldova : Country Financial Accountability Assessment - World Bank (Washington, DC, 2013)
The overall conclusion of this report is that despite some progress in improving public financial management, the financial accountability framework in Moldova is weak and requires substantial strengthening. This has important implications for both the Government and the Bank: the Government will need to make a significant effort over a long period of time to attend the issues identified within this report; and the Bank cannot rely on the Moldovan financial accountability framework to ensure that funds are spent for intended purposes, but rather the Bank will need to review and assess each operation's financial management risks and arrangements on its own merit. It would be unrealistic and impractical for the authorities to try to simultaneously address the many recommendations in this report. The Development Action Plan (DAP) lists and prioritizes the main recommendations of this CFAA. The overall responsibility for the implementation of the DAP rests with the Ministry of Finance however the Ministry of Economy, the Ministry of Labor, the Court of Accounts and the National Bank of Moldova also play significant roles. The DAP was endorsed by the National Steering Committee that was formed specifically for the purpose of this CFAA. The Board endorsed the CAS Progress Report in June 2002, which provided emphasis in public sector reforms and improving governance. The Government confirmed its commitment for strengthening governance by adopting a comprehensive public sector reform strategy. The strategy comprises three elements: (i) public administration reform; (ii) public expenditure management; and (iii) public/private interface. The CAS Progress Report recognized that Government has made significant progress in streamlining and improving public expenditure management, especially in the areas of budget execution, cash management, and debt management.